2023
DOI: 10.3390/ijms24054607
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids as Potential Wound-Healing Molecules: Emphasis on Pathways Perspective

Abstract: Wounds are considered to be a serious problem that affects the healthcare sector in many countries, primarily due to diabetes and obesity. Wounds become worse because of unhealthy lifestyles and habits. Wound healing is a complicated physiological process that is essential for restoring the epithelial barrier after an injury. Numerous studies have reported that flavonoids possess wound-healing properties due to their well-acclaimed anti-inflammatory, angiogenesis, re-epithelialization, and antioxidant effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 147 publications
1
54
0
2
Order By: Relevance
“…39 Numerous studies have demonstrated that the flavonoids and Carbopol 940 hydrogel possess wound-healing properties due to their well-acclaimed anti-inflammatory, antioxidant, re-epithelialization, and angiogenesis effects. 14,40–43 In our previous report, QU in combination with LU enhanced the antibacterial and antibiofilm efficacy synergistically, decreasing the membrane permeability and down-regulating the expression of multiple biofilm-related genes. 30 Besides, QU and LU are known for their powerful anti-inflammatory and antioxidant potency due to the resonance stability of the phenoxyl radical, 31,32 which support their potential use in wound healing.…”
Section: Discussionmentioning
confidence: 89%
“…39 Numerous studies have demonstrated that the flavonoids and Carbopol 940 hydrogel possess wound-healing properties due to their well-acclaimed anti-inflammatory, antioxidant, re-epithelialization, and angiogenesis effects. 14,40–43 In our previous report, QU in combination with LU enhanced the antibacterial and antibiofilm efficacy synergistically, decreasing the membrane permeability and down-regulating the expression of multiple biofilm-related genes. 30 Besides, QU and LU are known for their powerful anti-inflammatory and antioxidant potency due to the resonance stability of the phenoxyl radical, 31,32 which support their potential use in wound healing.…”
Section: Discussionmentioning
confidence: 89%
“…The micrograph of the nano bers seeded with cells showed that the L929 in sample 4 with 40% nano-encapsulated genistin and 150 min electrospinning time is best attached and proliferated on the nano bers. On one side, the avonoid structure of genistin and its immobilization in nano bers make it easily absorbed by L929 cells 37 ; on the other side, the hydrophilic two-component PVA/GE provides biochemical signals to promote cell adhesion, migration, proliferation, and differentiation 38 .…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…The healing time of diabetic wounds is longer due to an excessive and abnormal accumulation of several compounds like advanced glycation end products (AGEs) and reactive oxygen species (ROS), pro-/anti-inflammatory cytokines balance, interleukins, leukotrienes and complement factors at the wound site, but also to lack of ECM proteins [28]. The accumulation of AGEs can alter keratinocyte and fibroblast function.…”
Section: Pathology Of Diabetic Wound Healingmentioning
confidence: 99%
“…Much research has shown that flavonoids, such as curcumin, hesperidin, luteolin, quercetin, kaempferol, apigenin, rutin, naringin, morin, mangiferin have potential for the management of diabetic wounds through stimulation of ECM synthesis and angiogenesis, and modulation of growth factors (Table 1). Thus, curcumin accelerated the healing process by reducing inflammation and had an apoptotic effect in the early stages of wound healing [28]. Luteolin significantly reduced the expression of inflammatory factors, such as IL-1, IL-6 and TNF-α and reduced the levels of prostaglandin E2, interferon and leukotriene B4 [28].…”
Section: Flavonoidsmentioning
confidence: 99%